PROBLEMATIKA DAN KESIAPSIAGAAN PEMERINTAH DALAM PENANGANAN BENCANA - M, Mustainah; Royfandi, Moh (Universitas Riau, 2022)
Natural disasters are unpredictable and can come at any time so they need proper management. This study aims to determine disaster management of earthquakes, liquefaction, and flash flood in Sigi District. This study used the qualitative method. Data were collected by observation, interviews, and focus group discussions (FGD) involving government and communities determined using purposive sampling techniques. The results showed that there were various issues in disaster management in Sigi District, such as ineffective preparedness due to unimplemented early warning systems and preparedness plans as the disaster continued so that the simulation or training was also not effective. Meanwhile, the issue in terms of response was the delay in the provision of emergency assistance during the earthquake, liquefaction, and flash floods. In terms of recovery, there was a big issue regarding grants for the provision of permanent housing land for earthquake and liquefaction victims. The findings of this study add an indicator of communication in the aspect of disaster recovery due to miscommunication between the government, land agency, and the community regarding the provision of grants for permanent housing land for the earthquake and liquefaction victims